Svāmijiya patragaḷu : Śrī Svāmmi Vivēkānandara patragaḷa anuvāda - Vivekananda, Swami, 1863-1902 (SAMP early 20th-century Indian books project, 1947)
Letters of a Hindu religious leader of Ramakrishna order.